"Doing the month" and postpartum depression among Chinese women: A Shanghai prospective cohort study. Issue 2 (March 2020) - Ding, Guodong; Niu, Lei; Vinturache, Angela; Zhang, Jun; Lu, Min; Gao, Yu; Pan, Shuming; Tian, Ying; ,
Abstract: Background: The Chinese postpartum custom of "doing the month" characterized by generous social support available through the traditional cultural practices was considered to protect women from postpartum depression in early puerperium. Methods: This study used data from the Shanghai Birth Cohort, a study of 2615 postpartum women from Shanghai, China, that was conducted between 2013 and 2016. Detailed information on the traditional "doing the month" practices and the on the Edinburgh Postnatal Depression Scale scores was collected from questionnaires administered on the 42nd day after childbirth. Logistic regression models were used to examine the association between the adopting traditional puerperium practices and postpartum depression. Results: The estimated prevalence of postpartum depression in women from the Shanghai area in China was 11.8% (n = 308) at six weeks postpartum. Women who went outside their homes during the first month postpartum showed higher risks of postpartum depression compared with those who never left the house (1–2 times: OR = 1.9, 95% CI = 1.4–2.4; 3–5 times: OR = 2.3, 95% CI = 1.5–3.5; ≥6 times: OR = 2.5, 95% CI = 1.2–5.1). Women with average sleep of 6 h or less per night were more likely to suffer from postpartum depression compared with those who slept 8 h (6 h: OR = 1.7, 95% CI = 1.2–2.4; less than 6 h : OR = 3.3, 95% CI = 2.2–5.0). Women who opened the house windows most of the time exhibited decreased risks of postpartum depression compared to those who never or rarely opened the windows (often: OR = 0.6, 95% CI = 0.4–0.9; always: OR = 0.4, 95% CI = 0.3–0.7). Conclusions: Our results suggested that not all the activities of "doing the month" provided protection against developing PPD. This study emphasized the need for flexibility to fit and adjust the ritual into the modern life to enhance the positive effects of traditional practices on maternal health.